Strain relaxation in Fe3O4/MgAl2O4 heterostructures: Mechanism for formation of antiphase boundaries in an epitaxial system with identical symmetries of film and substrate - SHVETS, IGOR; ARORA, SUNIL (My University, 2009)
Strain relaxation studies in epitaxial magnetite, Fe3O4, thin films grown on MgAl2O4 100 substrates are reported. The study shows that the films were relaxed in line with the theoretical model prediction with a critical thickness, tc=5 nm. Antiphase boundaries APBs are not expected to form in Fe3O4 films grown on MgAl2O4 substrates because both film and substrate have the same crystal symmetry. In contrast, our study reveals the formation of APBs within the Fe3O4 films. Our analysis shows that the APBs in a Fe3O4 /MgAl2O4 heteroepitaxial system are formed by partial dislocations, which accommodate the misfit. This formation mechanism of APBs is fundamentally different from the one found in the Fe3O4 /MgO system, where APBs are formed as a consequence of equivalent nucleation sites on the MgO substrate separated by nontranslational vectors of the Fe3O4 lattice. The mechanism for the formation of antiphase boundaries through partial dislocations should be applicable to a wide range of epitaxial systems having identical symmetries of the film and the substrate and significant lattice mismatch.
PUBLISHED
Keywords: Atomic, molecular and chemical physics; MgO substrate; Nanoscience & Materials